ACTIVITY BASED COSTING METHOD AS THE BASIS FOR DETERMINING SERVICE RATES IN RADIOLOGY UNIT IN RSGM - Dwi Windu Kinanti; Retno Kusniati; Muhammad Hoesin Dwi Saputra (Universitas Muhammadiyah Yogyakarta, 2022)
In the construction of a Dental and Oral Teaching Hospital, the presence of the Faculty of Dentistry also played a role. In an effort to improve the quality of dentists and services to the wider community, each Faculty of Dentistry must have a Dental and Oral Hospital (RSGM). Operation-based costing is an accounting information system that describes the various activities carried out within an entity and collects costs associated with goods based on activities undertaken to produce, operate and distribute or assist the product concerned. To determine and realize dental and oral-service costs using the ABC method at the radiology unit of dental and oral hospital Unimus. This research is a qualitative descriptive case study design with an open-ended method in the form of Focus Group Discussion (FGD) with the chairman and management of dental hospital Unimus. Based on the results of the calculation of dental and oral-service costs at the radiology unit in Unimus Oral and Dental Hospital using the ABC method was Rp. 193.037 for Cephalometric Radiograph, Rp. 162.624 for Orthopantomographic (OPG), Rp. 138.181 for bitewing radiograph and Rp. 162.624 for temporomandibular joint radiograph (TMJ).